Reducing the erodibility of sandy soils engineered by cyanobacteria inoculation: a laboratory investigation - O'Kelly, Brendan (My University, 2023)
Windblown and water-induced erosion cause substantial soil losses worldwide, especially for drylands. Any sustainable management program that increases soil organic matter and improves the stability of the crustal layer could considerably enhance soil productivity and the preservation of erosion-prone land. This paper presents a laboratory investigation of cyanobacteria-inoculated medium sand and fine sand soils studied for severe runoff conditions that were simulated using an erosion function apparatus (EFA). Loosely deposited sand specimens prepared by air-pluviation were inoculated with a single native filamentous-cyanobacterium strain (investigating both Nostoc sp. and Calothrix sp.) and then incubated under high exposure to white light for 32- or 48-day periods. Well-developed bio-crusts were produced on the specimens’ top surface that achieved substantial improvements in erosion resistance, as was demonstrated for a wide range of hydraulic shear stress investigated using EFA experiments. Relative improvements in hydraulic erosion resistance were explained in terms of the nature of the cyanobacteria-developed microstructures (cyanobacteria filament infiltration of pore-void spaces and exopolysaccharide excretion), as were observed by scanning electron microscope examinations. The developed microstructure depended on the cyanobacterium strain employed and the nominal pore-void sizes that are related to the sand gradation and density state. The encouraging findings of this experimental investigation suggest a tailored approach (i.e., employing a suitable native cyanobacterium strain chosen for its compatibility with the soil’s physical properties) could lay the basis for developing a novel technology for soil protection.
PUBLISHED
Part of the Special Issue ?Sustainability in Geotechnics: The Use of Environmentally Friendly Materials?
Keywords: bio-crust; bio-geotechnics; erosion function apparatus; soil erosion; soil management; soil stabilization; wind erosion; International Development; Smart & Sustainable Planet; CYANOBACTERIA; EROSION; Environmental Geotechnics; GEOTECHNICAL ENGINEERING; Geotechnics; SOIL MODIFICATION; STABILIZATION; SURFACE EROSION; Soil Mechanics; Soil Sciences, Conservation; Soil Sciences, Erosion; bio-geotechnics; biocrust; drylands; geotechnical; soil improvement; soil stabilization